THE PROCESS OF DESERTIFICATION CAUSED BY CLIMATE CHANGE AND THEIR IMPACT ON GEORGIA'S BIODIVERSITY - Tea Mchedluri; Elene Petriashvili; Tinatin khokhobashvili (Innovate Conferences, 2025)
Different regions of Georgia respond uniquely to ongoing climate change, leading to varying levels of vulnerability. The country features a diverse natural landscape that has evolved over time. By the end of this century, climate change will remain a significant ecological and socio-economic challenge. It is a major driver of biodiversity loss. The projected increase in temperature and decrease in precipitation in Georgia are especially damaging to transitional ecosystems, altering the distribution of their flora and fauna.